Body ownership gates tactile awareness by reshaping the somatosensory functional connectivity - Alberto Pisoni; Carlotta Fossataro; Alice Rossi Sebastiano; Marcella Romeo; Eleonora Arrigoni; Leonor Josefina Romero Lauro; Nadia Bolognini; Francesca Garbarini (Proceedings of the National Academy of Sciences, 2025)
We all likely agree that tactile experience contributes to the emergence of the feeling of ownership over one’s own body. Is the opposite true? We answered this question by testing whether and how the sense of body ownership gates our tactile experience. In two experiments, we exploited a well-known multisensory illusion (Rubber Hand Illusion) to induce participants to feel a fake hand as belonging to their body, while their own hand was left in a disembodiment state (illusory-phases). After each illusory phase, a tactile stimulus was delivered to either the fake (embodied) hand or the real (disembodied) hand (testing-phases). Experiment 1 shows that the illusory phase significantly modulates the subjective feeling of touch experienced in the testing-phase, increasing tactile sensations when participants observed the fake (embodied) hand being touched (visual-touch), and decreasing them when the real (disembodied) hand was touched (real-touch). Experiment 2 investigated, by using TMS-EEG, the neural mechanism supporting this diametrical modulation of subjective feeling of touch, focusing on alpha-band oscillatory networks as the neural correlate of somatosensory awareness. S1 alpha-band connectivity fully matches the behavioral results, significantly increasing in visual-touch and decreasing in real-touch. In both experiments, a greater embodiment experienced in the illusory-phase significantly predicted higher behavioral and neurofunctional responses to visual-touch and lower responses to real-touch in the testing-phase. Altogether, our findings demonstrate that the sense of body ownership exerts a top-down modulation on tactile awareness and may do so by increasing or decreasing the strength of the somatosensory network involved in tactile awareness.